Hyaluronan-binding protein 2 (HABP2) gene variation in women with recurrent miscarriage - Frida Husseini-Akram; Sally Haroun; Signe Altmäe; Lottie Skjöldebrand-Sparre; Helena Åkerud; Inger Sundström Poromaa; Britt-Marie Landgren; Anneli Stavreus-Evers (BMC, 2018)
Abstract Background Idiopathic recurrent miscarriage, defined as three or more consecutive miscarriages, is a distressing early pregnancy complication. Although, the etiology of recurrent miscarriage is still unknown, an aberrant regulation of the endometrial receptivity marker hyaluronan-binding protein 2 (HABP2) has been suggested. The objective of the present study was to investigate the effect of genetic variations of HABP2 in women with idiopathic recurrent miscarriage compared to fertile women. Methods This study was designed as a case-control study. In total, 165 women who had three or more consecutive miscarriages and 289 fertile women were included in the study. Polymorphisms in the HABP2 gene were analyzed using TaqMan SNP Genotyping Assays. Three polymorphisms in the HABP2 gene, rs1157916, rs2240879 and rs7080536 (Marburg I) were studied. Results Polymorphism in HABP2 showed no significant difference in women with recurrent miscarriage compared to fertile women, except for rs1157916 minor A allele that was more prevalent among RM patients (p = 0.058). Significantly higher live birth rate was observed among women with three to four miscarriages compared to those with more miscarriages (p = 0.001). Conclusions Variations in the HABP2 gene did not seem to be involved in the etiology of recurrent miscarriage, while, the number of previous miscarriages had an impact on the live birth rate.